Outcomes of Revision Surgery Following Instrumented Posterolateral Fusion in Degenerative Lumbar Spinal Stenosis: A Comparative Analysis between Pseudarthrosis and Adjacent Segment Disease - Suh, Seung-Pyo (Asian Spine J, 2017)
STUDY DESIGN: Retrospective study. PURPOSE: We examined the clinical and radiological outcomes of patients who received revision surgery for pseudarthrosis or adjacent segment disease (ASD) following decompression and instrumented posterolateral fusion (PLF). OVERVIEW OF LITERATURE: At present, information regarding the outcomes of revision surgery for complications such as pseudarthrosis and ASD following instrumented PLF is limited. METHODS: This study examined 60 patients who received PLF for degenerative lumbar spinal stenosis and subsequently developed pseudarthrosis or ASD leading to revision surgery. Subjects were divided into a group of 21 patients who received revision surgery for pseudarthrosis (Group P) and a group of 39 patients who received revision surgery for ASD (Group A). Clinical outcomes were evaluated using the visual analogue scales for back pain (VAS-BP) and leg pain (VAS-LP), the Korean Oswestry disability index (K-ODI), and each patient's subjective satisfaction. Radiological outcomes were evaluated from the extent of bone union, and complications in the two groups were compared. RESULTS: VAS-LP at final follow-up was not statistically different between the two groups (p =0.353), although VAS-BP and K-ODI at final follow-up were significantly worse in Group P than in Group A (all p <0.05), and only 52% of the patients in Group P felt that their overall well-being had improved following revision surgery. Fusion rates after the first revision surgery were 71% (15/21) in Group P and 95% (37/39) in Group A (p =0.018). The rate of reoperation was significantly higher in Group P (29%) than in Group A (5%) (p =0.021) due to complications. CONCLUSIONS: Clinical and radiological outcomes were worse in patients who had received revision surgery for pseudarthrosis than in those who had revision surgery for ASD. Elderly patients should be carefully advised of the risks and benefits before planning revision surgery for pseudarthrosis.